2017
DOI: 10.1159/000485618
|View full text |Cite
|
Sign up to set email alerts
|

Platinum-Based Neoadjuvant Chemotherapy versus Primary Surgery in Ovarian Carcinoma International Federation of Gynecology and Obstetrics Stages IIIc and IV: A Systematic Review and Meta-Analysis

Abstract: Background/Aim: This study aimed to compare neoadjuvant chemotherapy (NAC) followed by interval debulking surgery (IDS) with primary debulking surgery (PDS) followed by chemotherapy in patients with advanced ovarian carcinoma International Federation of Gynecology and Obstetrics (FIGO) stages IIIc and IV. Methods: PubMed, the Cochrane Library, and manual searches were applied to discriminate potentially eligible studies published before June 30, 2016. Results: A total of 12 comparative studies were finally inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…We found a survival benefit of upfront surgery over NACT, with an additional 33 months of OS in patients undergoing PDS compared with patients undergoing early IDS or DDS. Our findings are concordant with several previous reports showing that upfront cytoreduction offers a survival benefit over IDS [ 4 5 29 30 ]. Hypothetically, delaying CRS after NACT promotes the selection of chemoresistant tumor cells, as the probability of developing chemoresistance increases with the increasing number of tumor cells.…”
Section: Discussionsupporting
confidence: 93%
“…We found a survival benefit of upfront surgery over NACT, with an additional 33 months of OS in patients undergoing PDS compared with patients undergoing early IDS or DDS. Our findings are concordant with several previous reports showing that upfront cytoreduction offers a survival benefit over IDS [ 4 5 29 30 ]. Hypothetically, delaying CRS after NACT promotes the selection of chemoresistant tumor cells, as the probability of developing chemoresistance increases with the increasing number of tumor cells.…”
Section: Discussionsupporting
confidence: 93%
“…Optimal cytoreduction is a critical prognostic factor for prolonged survival, whether it is performed before or after chemotherapy. Recent studies have suggested that NACT have reduced morbidity after surgery and are more suitable for optimal debulking surgery [9, 1113, 27, 28]. NACT followed by IDS (NACT-IDS) is considered to be an alternative to conventional PDS for treating advanced ovarian cancer patients and expected to have better prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, there were approximately 230 000 new cases in 2012 and the death toll was 150 000 [ 21 ]. Primary cytoreductive surgery and platinum-based adjuvant chemotherapy are still the criterion standard treatment for EOC patients [ 22 ]. However, most of these patients were diagnosed in the advanced stage, and half of the patients relapsed within 16 months, with a 5-year overall survival rate of less than 50% [ 23 26 ].…”
Section: Resultsmentioning
confidence: 99%